Direct reconstruction of the Reionization history from 21cm 2D Power Spectra - Pietschke, Yannic; Heneka, Caroline; Schlenker, Tom; Ore, Ayodele; Schosser, Benedikt (Journal of cosmology and astroparticle physics, 2025)
The 21cm line from the spin-flip transition of neutral hydrogen (HI) provides a unique window into the Epoch of Reionization (EoR), the final phase transition of our Universe. The Square Kilometre Array (SKA) enables precise measurements of 21cm fluctuations that trace ionization, temperature, and density fluctuations of the intergalactic medium (IGM). Nevertheless, a direct reconstruction of the timeline of the EoR in terms of the progress of ionization remains an ongoing challenge due to the highly non-Gaussian nature and thus intractable likelihood of the 21cm signal. Here, we present EoRFlow, a simulation-based inference (SBI) framework for reconstructing the global neutral hydrogen fraction x HI(z) directly from 2D cylindrically averaged power spectra (2DPS) of the 21cm signal. We validate our method on realistic mock datasets for SKA-Low. Bypassing the need for explicit likelihood formulations, our approach enables fast, unbiased posterior estimation of the x HI evolution in narrow redshift slices, allowing for piecewise reconstruction of the global reionization history. By directly inferring the reionization history from 21cm power spectra, our framework provides a scalable and robust path forward for 21cm cosmology in the SKA era.